God and the universe in the Vedāntic theology of Rāmānuja : a study in his use of the self-body analogy - Lott, Eric J. (Ramanuja Research Society, 1976)
Study on the philosophy of Ramanuja, founder of qualified non-dualistic (Vishistadvaita) school of Hindu philosophy.